Economic Short-circuit in Costa Rica During the Twenty-first Century (Revista Rupturas, 2019)
The main structural problems that limit the economic growth and the inequalities are analyzed. The issue is addressed from the power networks of the economic power groups, the unemployment, the indebtedness of families and the imbalance of the public finances. This through the narrative of the short-circuit, referring to a connection that fails and therefore the system starts to malfunction.
Keywords: elite; networks of power; neoliberalism; unemploymente; inequalities